INTEGRATED COASTAL MANAGEMENT IN VIETNAM: CURRENT SITUATION AND ORIENTATION - Cuong, Nguyen Quoc; Cu, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2014)
Vietnam is a coastal country located along the Vietnamese East Sea, has a coastline longer than 3,260 km, with two archipelagoes of Hoang Sa (Paracel islands) and Truong Sa (Spratly islands) and more than 3,000 big and small islands, with 28 coastal provinces and cities of 63 provinces and cities of the country. The coastal area accounts for 17% of the total area of ​​the country, and is inhabited by more than 20 million people, with the average population density of about 267 people per km², 1.2 times higher than average density of the country. Marine resources and advantages promise great prospects for the development of ocean and coastal economies of the country. However, along with the development and some achieved successes, we also face to many serious problems and challenges in marine environment, that tends to increase. Therefore, the application of integrated coastal management approach is of paramount importance for the sustainable development of ocean and coastal economic of Vietnam. In recent years, with the support of the international organizations and countries from ASEAN region, Vietnam has been trying to enhance the application of integrated coastal management for the entire coastal area. Beside the achievements, practical application of integrated coastal management also indicates many difficulties and challenges, required to make timely solutions. In this paper, we are looking forward to sharing information and the experience of integrated coastal management in Vietnam and do hope to receiving more supports from international and regional organizations for Vietnam to adopt successfully and efficiently integrated ocean and coastal management approach, and implement Vietnam's commitments in the implementation of sustainable development strategy for the East Asian Sea (SDS-SEA).